Avaliação da qualidade da água para o consumo humano do município de Manicoré-AM - Lima, Eliezer Lucio Fernandes (Brasil, 2024)
Assessing the quality of water for human consumption is extremely important due to the crucial role that water plays in the health of the population. The population that consumes quality water is free from waterborne diseases. However, human actions through industrial, agricultural and urban expansion pose a danger to water bodies and groundwater. Therefore, the objective of this study was to evaluate the quality of water for human consumption in the municipality of Manicoré/AM. A survey of the semi-artesian wells that supply the city was carried out, and then the collection points were georeferenced. Collection took place during the rainy season, and 6 (six) sampling points were selected, from which the following parameters were determined: a) microbiological: thermotolerant coliforms and total coliforms; b) physical: apparent color and turbidity; c) chemicals: iron and total manganese. After laboratory analyses, the results were compared with the values established in Ordinance No. 888/2021 of the Ministry of Health. The results indicated that point 6, located in the Santa Luzia neighborhood, revealed the presence of total and thermal coliforms, as well as Also, values above those allowed were found for the apparent color and turbidity variables. Point 1, located at the Municipal guard post, in the Manicorézinho neighborhood, also indicated the presence of total coliforms. The evaluation of the parameters of both points studied (1 and 6) demonstrated that the water from the wells obtained values that do not comply with those established, thus being characterized as unsuitable for human consumption.